Introduction to kinesiology studying physical activity - Hoffman, Shirl J. (Human Kinetics, 2013)
Offers an introduction to the field of sport science available and provides students a solid background in the subject and prepares them for further study and course work. This title acknowledges the diverse interests and aspirations that students have in pursuing professional and scholarly careers as well as teaching or coaching.